(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Spathodea campanulata, well known for its traditional medicinal uses was investigated for hepatoprotective activity against acetaminophen-induced hepatic damage in mice. Six groups of mice were pre-treated with 100, 300 and 625 mg/kg of the aqueous extract of Spathodea campanulata stem bark, N-acetyl cysteine (300 mg/kg; p.o) or distilled water for 5 days before they were intoxicated with a single dose of acetaminophen (600 mg/kg; p.o). Alanine aminotransferase, Aspartate aminotransferase and total protein levels were measured in serum, glutathione peroxidase, superoxide dismutase and total cytochrome P450 levels were measured in liver homogenate and liver histology was also observed on liver sections. Total liver cytochrome P450 levels in Spathodea campanulata extract, distilled water, ketoconazole or phenobarbital-treated animals were also measured. Significant hepatoprotection was obtained against liver damage induced by acetaminophen as evident from decreased serum levels of Aspartate transaminase, Alanine transaminase and increased levels of total protein in the combined acetaminophen and extract treated groups and the acetaminophen and N-acetylcysteine-treated groups compared to the acetaminophen only controls. The decrease in serum antioxidant enzymes; glutathione peroxidase and superoxide dismutase levels caused by acetaminophen was significantly reversed by the extract. The results correlated well with the histopathology of liver from treated and control animals. The extract also caused considerable inhibition of total CYP450, the enzymes involved in the activation of acetaminophen. The present results indicate that Spathodea campanulata protects the liver against acetaminophen-induced hepatotoxicity by enhancing antioxidant protection capacity and interfering with the bio-activation of acetaminophen.